The last of the Mohicans - Cooper, James Fenimore 1789-1851; Warren, Eliza Gatewood; Pablo Marcos Studio (Edina, Minn ABDO Pub, 2002)
In 1757, the third year of the French and Indian War, Hawkeye, a colonial scout, and his friends, Chingachkook, a chief of the Mohicans, and his son Uncas risk their lives to guide two English sisters through hostile territory and evade the evil Huron, Magua, who is determined to destroy them
Originally published: New York : Playmore : Waldman Pub., 1990
1
Keywords: Mohegan Indians -- Juvenile fiction; Indians of North America -- East (U.S.) -- Fiction; Mohegan Indians -- Fiction; United States -- History -- French and Indian War, 1755-1763 -- Juvenile fiction; United States -- History -- French and Indian War, 1755-1763 -- Fiction